Estimating the clinical impact of introducing paediatric influenza vaccination in England and Wales - White, L; Sculpher, M; Pitman, L (Elsevier, 2011)
Influenza causes a significant burden of disease each year in England and Wales, with the young and the elderly suffering the greatest burden. Children are recognised as playing an important role in the dissemination of the influenza virus. This study examines the population impact of implementing a programme of paediatric vaccination. A dynamic transmission model was used to simulate the impact of vaccination programmes with varying levels of coverage across pre-school and school age children. These analyses suggest that vaccinating as few as 50% of 2–18 year olds could result in a substantial reduction in the annual incidence of influenza related morbidity and mortality across the population. Herd immunity may extend this protection to the young and the elderly. It is assumed that such programmes would be implemented in concert with the current strategy of vaccinating the elderly and younger at risk groups with an inactivated vaccine. In England and Wales, paediatric vaccination of two to eighteen year olds reduced the estimated number of general practice consultations, hospitalisations and deaths arising from influenza A and B infections by up to 95%. This translates into an annual average reduction of approximately 52,000, 1500 and 1200 events, respectively. A policy of paediatric vaccination could significantly reduce the clinical burden of influenza in England and Wales, in all age groups, with the added value of herd immunity helping to protect the young and the elderly who are at highest risk of complications. Highlights: ► Children play an important role in the dissemination of the influenza virus. ► Vaccinating 50% of 2–18 year olds could significantly reduce the influenza burden. ► Preventing 52,000 GP consultations, 1500 hospitalisations and 1200 deaths annually. ► Herd immunity can help to protect those at highest risk of complications.